ڈاکٹر خورشید رضوی کا ترجمہ ’’تاریخ علوم میں تہذیب اسلامی کا مقام‘‘ :تحقیقی و تنقیدی جائزہ: Dr. Khurshid Rizvi’s translation “Tāreekh-e-ʻUloom mein Tahzeeb-e-Islamī Kā Muqām”: An Analytical Study (Al-Qamar, 2020)
Dr. Khurshid Rizvi is a well-known and Eminent literary and cultural personality of present Era. He is multi-dimensional and versatile writer of Urdu. His valuable literary work comprises on poetry, research and Editing, criticism, sketch writing, translation and essay writing. He earned world-wide recognition for his great literary works in Urdu and Arabic. His writing style, language and diction is very unique and impressive. He has full command and grip over Urdu, Arabic, Persian and English languages. This article is all about of his creativity, remarkable research work and translation. He translated the famous historical lectures of Dr. Fawad Sezgin under the German title (Geschichte des Arabischen Shrifttums). Dr. Fawad Sezgin (1924–2018) is a renowned contemporary Muslim Scholar, researcher and orientalist. He was originally from Turkey but spent most of his time in Germany. He has done his research work mostly in German Language. He learned a lot from great orientalists Hellmut Ritter and Carl Brockelmann. He had devoted his life to Islamic-Arabic Science History. Basically in his thirteen lectures delivered in Saudi Arabia, in 1979, he highlighted the remarkable research works of Arab-Muslims in the field of Social and Natural Sciences before the period of Renaissance. He presented true appraisal about the contribution of Muslim Scholars, Scientists and Philosophers. He also pointed out some misunderstandings of Western orientalists who denied and tempered the Muslims contributions towards Historical tradition of knowledge and philosophy.This valuable research work was originally in German Language and later on it has been translated in Arabic language under the name of تاریخ التراث العربی (عربی ورثے کی تاریخ). Dr. Khurshid Rizvi translated these thirteen lectures (محاضرات   فی تاریخ العلوم العربیہ والاسلامیہ) from Arabic into Urdu under the title (تاریخ علوم میں تہذیب اسلامی کا مقام). It was published by Idara Tahqeeqat-e-Islami, International Islamic University Islamabad in 1994.
Keywords: Khurshid Rizvi; Fawad Sezgin; History of Arabic Heritage; Muslim Civilization; Natural Sciences; Western Scholars